Initial and Middle-Term Outcome of Treatment for Spontaneous Isolated Dissection of Superior Mesenteric Artery. Issue 45 (November 2015) - Li, Zilun; Ding, Huanyu; Shan, Zhen; Du, Jianliang; Yao, Chen; Chang, Guangqi; Wang, Shenming
Abstract : Abstract: Symptomatic isolated dissection of the superior mesenteric artery (SIDSMA) represents an extremely rare condition. Although various treatments including conservative treatment, endovascular stenting (ES), and surgical repair are currently available, consensus treatment guideline is absent due to scarce of SIDSMA cases. Thus, we present our experience in the treatment of SIDSMA at our single center. Fourteen cases of SIDSMA were treated with conservative treatment, catheter-directed thrombolysis (CDT), endovascular stenting (ES), or surgical repair at our center between January 2008 and January 2014. Demographics, clinical manifestations, coexisting medical conditions, imaging feature, treatments, and follow-up outcome of these patients were retrospectively collected and analyzed. For 13 patients without peritonitis, conservative treatment was given for 4 to 6 days initially. After the first observation cycle, symptoms and signs were alleviated in 8 patients, and conservative treatments were continued. The remaining 5 patients received technically and clinically successful ES (in 4) or CDT (in 1) due to worsening symptoms and signs during conservative treatment. One patient with peritonitis underwent emergency surgery, with the necrotic small intestine resected. However, the abdominal pain was not alleviated 17 days postoperatively, ES was thus performed and symptoms relieved immediately. Two weeks after ES, a new aneurysm and partial thrombosis in the distal part of the stent were found by computed tomography angiography in this patient. No intestinal infarction or mortality developed during hospitalization. Follow-up was accomplished in 11 cases, ranging from 4 to 74 months (23.5 ± 21.3). Except that one complained with mild abdominal pain, the other 10 achieved complete remission. All patients were free from new aneurysmal formation of SMA and all stents remained patent. For SIDSMA without peritonitis, conservative treatment can be provided with reasonable success rate, while ES may serve as an effective alternative once conservative treatment fails. For SIDSMA with peritonitis, open surgery remains the treatment of choice by resection of necrotic intestine and revasculization.